Effectiveness of Jigsaw Type Cooperative Learning Model on Mathematical Problem Solving Ability Viewed from Student Learning Motivation - Rahmawati, Rina; Pujiastuti, Emi (Unnes Journal of Mathematics Education, 2023)
Mathematical problem-solving skills are one of the main things in learning mathematics and must be developed in students. One of the learning models that is effective and considered capable of improving and improving mathematical problem-solving skills is the jigsaw-type cooperative learning model. This study aims to determine the effectiveness of the jigsaw-type cooperative learning model on mathematical problem-solving ability, analyze the influence of learning motivation on students' mathematical problem-solving ability on the jigsaw-type cooperative learning model, and describe mathematical problem-solving ability in terms of learning motivation in the jigsaw-type cooperative learning model. This study used mixed methods with a sequential explanatory design. The population of this study was all grade VII students of SMP N 1 Tambakromo for the 2021/2022 School Year. This research sample was obtained using a class random technique, namely class VII C students as an experimental group and class VII A students as a control group. There were 6 qualitative subjects drawn from the experimental group, namely 2 students with high learning motivation, 2 students with moderate learning motivation, and 2 students with low learning motivation. The results showed that (1) The jigsaw-type cooperative learning model is effective on students' mathematical problem-solving abilities; (2) There was a positive influence of student learning motivation on mathematical problem-solving ability in the jigsaw-type cooperative learning model of 48.4%; and (3) students with high learning motivation have high problem-solving ability, students with moderate learning motivation have moderate problem-solving ability, while students with low learning motivation.